2018
DOI: 10.1038/s41586-018-0272-2
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous tropical and polar temperature evolution in the Eocene

Abstract: Palaeoclimate reconstructions of periods with warm climates and high atmospheric CO concentrations are crucial for developing better projections of future climate change. Deep-ocean and high-latitude palaeotemperature proxies demonstrate that the Eocene epoch (56 to 34 million years ago) encompasses the warmest interval of the past 66 million years, followed by cooling towards the eventual establishment of ice caps on Antarctica. Eocene polar warmth is well established, so the main obstacle in quantifying the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

23
301
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 246 publications
(363 citation statements)
references
References 102 publications
(153 reference statements)
23
301
3
Order By: Relevance
“…Indeed, the dependence of feedbacks on baseline temperature highlighted in this work provide a plausible explanation for why Anagnostou et al () found a higher climate sensitivity (∼4 °C per CO 2 doubling) in the relatively warm early Eocene climatic optimum than in the relatively cool late Eocene (∼3 °C per CO 2 doubling). Our findings are also consistent with Cramwinckel et al (, their Extended Data Figure 9), who, relative to the late Eocene, find a higher sensitivity for the warm EECO than for the cooler middle Eocene.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Indeed, the dependence of feedbacks on baseline temperature highlighted in this work provide a plausible explanation for why Anagnostou et al () found a higher climate sensitivity (∼4 °C per CO 2 doubling) in the relatively warm early Eocene climatic optimum than in the relatively cool late Eocene (∼3 °C per CO 2 doubling). Our findings are also consistent with Cramwinckel et al (, their Extended Data Figure 9), who, relative to the late Eocene, find a higher sensitivity for the warm EECO than for the cooler middle Eocene.…”
Section: Resultssupporting
confidence: 93%
“…The change in global climate sensitivity over time includes a gradual increase in sensitivity from the earliest Cretaceous to the latest Cretaceous, a decrease to a minimum in the Paleocene, and then an increase followed by a decrease in the Eocene. Our modeled range of climate sensitivities in the Eocene (3.8 to 4.7 °C) is consistent with estimates of 3.5 to 8.9 °C (Cramwinckel et al, ) and 2.9 to 4.0 °C (Anagnostou et al, ), inferred from temperature and CO 2 proxies for this time period.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations